Aluminum Corrosion Analysis for Environmental Acid Chloride Solution - Arwati, I Gusti Ayu; Fina, Fina (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
Aluminum is the most commonly used metal. Aluminum is present on the bipolar plate which is a key part in PEMFC (Proton Exchange Membrane Fuel Cell). In the air, aluminum is easily oxidized, forming a thin layer (Al2O3). Therefore it's necessary to do an experiment to find out the extent of corrosion on aluminum. In this experiment, corrosion rate analysis on aluminum is arrived at by using hydrochloric acid (HCl) using weight loss and electrochemical methods. And corrosion rate results of aluminum metal with a concentration of 0.1M ; 0.2M; 0.3M; 0.4M and 0.5M with a concentration of 0.5M with a value 0.04250 grams and the smallest corrosion rate of 0.00030 gram with concentration of 0,1M. The largest value of corrosion rate at 0.58610 (mpy) and 0.91589 Ampere using electrochemical method. Morphology on aluminum is seen using SEM (Scanning Electron Microscope is pitting corrosion).